Guilt Aversion in (New) Games: Does Partners' Payoff Vulnerability Matter? - Giuseppe Attanasi; Claire Rimbaud; Marie Claire Villeval (Institute of Labor Economics (IZA), 2023)
We investigate whether a player's guilt aversion is modulated by the co-players' vulnerability. To this goal, we introduce new variations of a three-player Trust game in which we manipulate payoff vulnerability and endowment vulnerability. The former is the traditional vulnerability which arises when a player's material payoff depends on another player's action (e.g., recipient's payoff in a Dictator game). The latter arises when a player's initial endowment is entrusted to another player (e.g., trustor's endowment in a Trust game). Treatments vary whether trustees can condition their decision on the belief of a co-player who is payoff-vulnerable and/or endowment-vulnerable, or not vulnerable at all, and the decision rights of the vulnerable player. We find that trustees' guilt aversion is insensitive to the dimension of the co-player's vulnerability and to the decision rights of the co-player. Guilt is activated even absent vulnerability of the co-player whose beliefs are disappointed. It is triggered by the willingness to respond to the co-player's beliefs on his strategy, regardless of whether this strategy concerns this player or a third player's vulnerability, that is, indirect vulnerability.
Keywords: C72; C91; D91; 330; guilt aversion; vulnerability; psychological game theory; Dictator game; Trust game; experiment